2019
DOI: 10.1590/0103-6440201902801
|View full text |Cite
|
Sign up to set email alerts
|

The Wear Performance of Glazed and Polished Full Contour Zirconia

Abstract: This study evaluated the influence of zirconia surface finishes on the wear of an enamel analogue. 40 zirconia discs were divided into four groups: control (without finish); glazed; polished; polished and glazed. All samples were subjected to wear against steatite antagonists. The specimens underwent roughness, topographic, scanning electron microscopy (SEM) and wettability analyses. Quantitative wear measurements were performed on both steatites and discs. To measure wear of steatites the weight before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The specimens were simultaneously thermocycled (1000 cycles, 60-second holding time, 15-second transfer time, and 5 C and 55 C). [54][55][56] The CAD-CAM specimens and enamel antagonists were scanned before (baseline) and after the wear test (follow-up) 2,53 by using an intraoral scanner (CEREC Omnicam 4.4.1; Dentsply Sirona) to obtain standard tessellation language (STL) files (Figs. 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were simultaneously thermocycled (1000 cycles, 60-second holding time, 15-second transfer time, and 5 C and 55 C). [54][55][56] The CAD-CAM specimens and enamel antagonists were scanned before (baseline) and after the wear test (follow-up) 2,53 by using an intraoral scanner (CEREC Omnicam 4.4.1; Dentsply Sirona) to obtain standard tessellation language (STL) files (Figs. 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al [4] found that more wear was found in teeth opposing dental porcelain and claimed that the addition of porcelain composite during the glaze process of zirconia is the reason behind their results. On the contrary, Alves et al [48], found that the glaze surface finish of zirconia caused less wear on antagonists that the polished ones. Their explanation was that due to the thinness and homogeneity of the glaze layer, it abraded quickly forming no debris due to fracture and caused less abrasiveness to the antagonist [48].…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, Alves et al [48], found that the glaze surface finish of zirconia caused less wear on antagonists that the polished ones. Their explanation was that due to the thinness and homogeneity of the glaze layer, it abraded quickly forming no debris due to fracture and caused less abrasiveness to the antagonist [48]. Another contradicting study was that of Passos et al [30], who found that more material wear was found in polished ceramic samples than glazed ones, they claimed that the glaze layer formed a protection to the ceramic surface and exhibited fewer cracks.…”
Section: Discussionmentioning
confidence: 95%
“…Glazing is formed by burning a thin, transparent silica glass coating on the surface or by firing the substructure up to the proper temperature for a few minutes to obtain a glossy ceramic surface [ 10 ]. Furthermore, glazed monolithic zirconia wears opposing teeth less than polished zirconia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%